Serum Krebs von den Lungen‐6 level in the disease progression and treatment of Mycobacterium avium complex lung disease. Issue 1 (29th June 2020) - Asakura, Takanori; Kimizuka, Yoshifumi; Nishimura, Tomoyasu; Suzuki, Shoji; Namkoong, Ho; Masugi, Yohei; Sato, Yasunori; Ishii, Makoto; Hasegawa, Naoki
ABSTRACT: Background and objective: The lack of useful biomarkers reflecting the disease state limits the management of Mycobacterium avium complex lung disease (MAC‐LD). We clarified the associations between serum KL‐6 level, disease progression and treatment response. Methods: Resected lung tissues from MAC‐LD patients were immunostained for KL‐6. We compared serum KL‐6 levels between MAC‐LD and healthy control or bronchiectasis patients without nontuberculous mycobacterial lung disease (NTM‐LD). Serum KL‐6 level was assessed in a prospective observational study at Keio University Hospital between May 2012 and May 2016. We investigated associations between serum KL‐6 level and disease progression and treatment response in patients untreated for MAC‐LD on registration ( n = 187). Results: The KL‐6 + alveolar type 2 cell population in the lung and serum KL‐6 level were significantly higher in MAC‐LD patients than in controls. Serum KL‐6 level in bronchiectasis patients without NTM‐LD showed no significant increase. Of the 187 patients who did not receive treatment on registration, 53 experienced disease progression requiring treatment. Multivariable Cox analysis revealed that the serum KL‐6 level (aHR: 1.18, P = 0.005), positive acid‐fast bacilli smear (aHR: 2.64, P = 0.001) and cavitary lesions (aHR: 3.01, P  < 0.001) were significantly associated with disease progression. The change in serum KL‐6 (ΔKL‐6) was significantly higher in the disease progression group; it decreased post‐treatment, reflecting the negative sputum culture conversion. Conclusion: Serum KL‐6 level is associated with disease progression and treatment response. Longitudinal assessment combined with AFB smear status and presence of cavitary lesions may aid MAC‐LD management. Abstract : Serum Krebs von den Lungen‐6 (KL‐6) level is a useful serum biomarker that predicts disease progression and treatment response in Mycobacterium avium complex lung disease (MAC‐LD). Single and longitudinal assessment of serum KL‐6 level may aid the management of MAC‐LD and help establish management strategies for MAC‐LD.